INTERNATIONALIZATION OF STATE-OWNED ENTERPRISES THROUGH FOREIGN DIRECT INVESTMENT - Cahen,Fernanda Ribeiro (2015)
ABSTRACT State-owned enterprises (SOEs) are created to focus on domestic needs, and yet recent evidence points to increasing outward foreign direct investment by SOEs. Existing International Business (IB) theories focus on efficiency-based motives for internationalization; therefore, they do not fully capture SOEs' internalization dynamics, which are driven largely by political factors and social welfare considerations. We integrate public management and IB theories to develop propositions that combine these questions: why SOEs internationalize; what are their motivations; and what are the main managerial outcomes of SOEs' internationalization. Our findings suggest that SOEs display little hesitancy in entering international markets, and that SOE international expansion is not contradictory with the goals of state-ownership if the purpose is to adjust the company to changing institutional environments both in the domestic and international markets. Our propositions about SOE internationalization are based on an in-depth case study of the outward foreign direct investment conducted by Brazil's Petrobras over the past three decades.